Partial cross ownership and tacit collusion - Yossi Spiegel; David Gilo (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2003)
This paper shows how competing firms can facilitate tacit collusion by making passive investments in rivals. In general, the incentives of firms to collude depend in a complex way on the whole set of partial cross ownership (PCO) in the industry. We show that when firms are identical, only multilateral PCO may (but need not) facilitate tacit collusion. A firm?s controller can facilitate tacit collusion further by investing directly in rival firms and by diluting his stake in his own firm. In the presence of cost asymmetries, even unilateral PCO by efficient firms in a less efficient rival can facilitate tacit collusion.
Keywords: D43; L41; 330; partial cross ownership; repeated Bertrand oligopoly; tacit collusion; controlling shareholder; cost asymmetries; Kartell; Kapitalbeteiligung; Eigentümerstruktur; Wiederholte Spiele